A new species of Attheyella (Canthosella) from Colombia and redescription of Attheyella (Delachauxiella) freyi (Copepoda: Harpacticoida: Canthocamptidae) - Gaviria, Santiago; Defaye, Danielle (Zootaxa, 2012)
Occasional collections of organisms from water bodies of the Andean Region and the Pacific coast of Colombia yieldedtwo species of canthocamptid harpacticoids belonging to the genus Attheyella Brady, 1880. A new species, Attheyella(Canthosella) chocoensis n. sp., inhabiting phytotelmata of the forest at the Pacific Chocó State is described. Attheyella(Delachauxiella) freyi Löffler, 1963, described from Ecuador, was found in a high mountain pond in the southern Colom-bian Andes, and redescribed here. Both species are illustrated with line drawings and SEM photographs. A special mor-phological structure was discovered on the antenna of male and female Attheyella (D.) freyi: it is probably present in otherspecies of the subgenus Delachauxiella Brehm, 1926, as well. An identification key to Colombian species of the family Canthocamptidae is provided.